Fluoroless cavotricuspid isthmus radiofrequency ablation of typical atrial flutter achieves success with zero radiation and shorter procedural duration. (19th May 2022) - Jacinto, S; Silva Cunha, P; Portugal, G; Valente, B; Coutinho Cruz, M; Lousinha, A; Veiga, J; Delgado, AS; Bras, M; Paulo, M; Guerra, C; Teixeira, AR; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cavotricuspid isthmus (CTI) ablation in patients with typical atrial flutter (AFL) has improved in the past years, especially by the use of threedimensional (3D) electroanatomic mapping systems. These mapping tools contributed to reduce radiation exposure, but most ablation procedures still require varying amounts of fluoroscopy. Purpose: We aim to examine whether fluoroless CTI ablation is effective and safe in reducing AFL recurrence, compared with CTI ablation using fluoroscopy and a 3D mapping system. Methods: A retrospective analysis of CTI ablation procedures performed at a tertiary center between December 2008 and December 2020 was conducted. Cases were divided in two groups: fluoroless and fluoroscopic, according to the use of radiation. Procedural duration, fluoroscopy time (FT), use of 3D mapping system, complications and recurrence rate at one year were analyzed. Results: A total of 324 CTI ablations performed on patients with documented typical AFL were included. Mean age was 62.3±14.0, with 78.1% male patients. Fluoroless ablations were performed based on a 3D mapping system, and all fluoroscopic procedures also used 3D electroanatomic mapping. The FT was zero in the fluoroless group - 31 cases (9.6%), and 7.0±4.4 minutes in the fluoroscopic group - 291 cases (90.4%) (p<0.001). There was no statistically significant difference between the two groups, regarding AFL recurrence at one year (21.7% in the fluoroless group versus 13% in the fluoroscopic group; odds ratio [OD] 0.54; 95% confidence interval [CI] 0.18-1.62; p=0.27). Total procedure duration was significantly shorter in the fluoroless group (1h07m versus 1h40m; t-test 4.261, p<0.001, CI 0h16m-0h50m). There were no acute complications for both groups. Conclusion: Fluoroless CTI ablation avoids radiation exposure to the patient and operator and can be performed in patients with typical AFL, without compromising duration, safety or efficacy of the procedure.